The Relationship Between Knowledge And Preventive Behavior of Adhesive Capsulitis In Fried Rice Vendors In Denpasar City, Bali Province - I Gusti Ayu Widianti; Anak Agung Ayu Tri Pradnya Purantara; Yuliana Yuliana; Gede Wirata (International Journal Labs, 2026)
The culinary business, including fried rice vendors, had the potential to experience musculoskeletal complaints such as adhesive capsulitis (frozen shoulder), which was triggered by the lack of movement in the passive shoulder or movements inversely proportional to the activity of the opposite shoulder during work. Adhesive capsulitis was characterized by pain, stiffness, and loss of shoulder range of motion. Early management was important to prevent the disease from progressing to the frozen phase. A high level of knowledge could help an individual apply disease prevention behavior. This study aimed to analyze the relationship between knowledge and preventive behavior regarding adhesive capsulitis in the shoulders of cart-based fried rice vendors in Denpasar City, Bali Province. The research used an observational analytic design with a cross-sectional approach. The sample consisted of 40 cart-based fried rice vendors, selected using the purposive sampling technique. Data were collected through questionnaires and interviews. Data analysis was performed using the Spearman correlation test because the data scale was ordinal. The majority of respondents had a low level of knowledge (50.0%) and low preventive behavior (55.0%). The Spearman correlation test showed a significant (p=0.000), very strong (r=0.828), and unidirectional relationship between knowledge and preventive behavior regarding adhesive capsulitis. The conclusion of the study was that there was a significant, strong, and unidirectional relationship between knowledge and preventive behavior regarding adhesive capsulitis of fried rice vendors in Denpasar City, Bali Province.